THE LEVEL OF AWARENESS OF NURSING STUDENTS TO THE RETENTION and ELIMINATION POLICY: A BASIS FOR AN ORIENTATION PROGRAM - Abadingo, Aileen; Sanchez, Marc (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
As defined in various articles, student retention is the extent to which the learners stay in a Higher Education Institution and complete a program or course of study within a specified time. Retention at university matters. It matters morally, as we know the life chances of people who complete a degree are dramatically improved. It matters financially, as students who leave a university before graduation take their fees with them. And it matters nationally, as the higher the education level of the population, the greater the nation’s level of productivity and innovation. Despite all the information contained in the student’s manual, it is unclear whether students are aware of these policies necessary for the journey in the University. No such study existed at the moment of this writing. It should be noted that students must be aware of this information, so they are guided on the rules and regulations of a University. This brings us to the research questions on what is the level of awareness of UCLM nursing students of the University’s Retention and Elimination Policy. This is very important so that decisions can be made to further initiate more campaigns regarding the policy. a report emphasized the practices that improve student retention which include (A) addressing widening participation, and those focusing on the development of learning and teaching; (B) a focus on the context of institutional practice (Action on Access, 2003). In conclusion, initiatives and programs in organizations or institutions focusing on retention and elimination policies for the development of the student and the institution seem to be very crucial. The mean scores yielded 2.324 and 2.6 which is interpreted as a low level of awareness as stated in the descriptive interpretation. Students have poor knowledge of these policies which could be crucial for them moving forward. Therefore, the measurement findings of this study highlight how the application of an orientation program and how affects their level of awareness of policies in general. Programs in orientation programs and distribution of student manuals for information dissemination as mentioned earlier in the paragraph should be increased. Promoting these activities should increase the level of understanding of the students. The consequences will lead to a lowering of student engagement and most likely lead to attrition.